2023
DOI: 10.1126/sciimmunol.abn4332
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-resident memory T cells mediate mucosal immunity to recurrent urinary tract infection

Abstract: Urinary tract infection (UTI) is one of the most prevalent human bacterial infections. New therapeutic approaches, including vaccination and immunotherapy, are urgently needed to combat the rapid global dissemination of multidrug-resistant uropathogens. Development of therapies is impeded by an incomplete understanding of memory development during UTI. Here, we found that reducing bacterial load early in infection, by reducing the inoculum or with antibiotics after infection, completely abrogated the protectiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…A recent study showed that, in a mouse model of recurrent UTI, bladder tissue-resident memory T cells (T rm ) are both necessary and sufficient for developing immune memory. 120 Interestingly, the authors found no T H subset cell skewing among CD 4 + T cells in bladder and draining lymph nodes post infection. Instead, a mixture of T H 1, T H 2, T H 17, and T reg cells was detected over 7 days of infection.…”
Section: Immune Responses or Host Responses To Expec Vaccinesmentioning
confidence: 92%
See 4 more Smart Citations
“…A recent study showed that, in a mouse model of recurrent UTI, bladder tissue-resident memory T cells (T rm ) are both necessary and sufficient for developing immune memory. 120 Interestingly, the authors found no T H subset cell skewing among CD 4 + T cells in bladder and draining lymph nodes post infection. Instead, a mixture of T H 1, T H 2, T H 17, and T reg cells was detected over 7 days of infection.…”
Section: Immune Responses or Host Responses To Expec Vaccinesmentioning
confidence: 92%
“… 120 Additionally, mice that lack mature B cells achieved a level of bacterial clearance comparable to wild-type mice during reinfection, suggesting that B cells are dispensable for UTI memory. 120 Another mouse study also pointed out that T H 1 cells instead of serum IgG are responsible for the increased bacterial clearance induced by vaccination. 117 As most past vaccine studies have considered B cell antibody response as a hallmark for protection, these findings question the paradigm and highlight the protective role of T cells in immune memory.…”
Section: Immune Responses or Host Responses To Expec Vaccinesmentioning
confidence: 99%
See 3 more Smart Citations